2004
DOI: 10.1177/1073191104268029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mindfulness by Self-Report

Abstract: A self-report inventory for the assessment of mindfulness skills was developed, and its psychometric characteristics and relationships with other constructs were examined. Participants included three samples of undergraduate students and a sample of outpatients with borderline personality disorder Based on discussions of mindfulness in the current literature, four mindfulness skills were specified: observing, describing, acting with awareness, and accepting without judgment. Scales designed to measure each ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
583
1
41

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,677 publications
(702 citation statements)
references
References 39 publications
41
583
1
41
Order By: Relevance
“…For some, the C-CELE reshaped their sociocultural context. This study's findings correlated with Baer, Smith, and Allen (2004), who revealed that experiential situations heighten emotional reaction and that emotional reaction toward content in association with experience generated profound levels of knowledge acquisition, which, according to the data from this study, had positive repercussions that transferred into awareness.…”
Section: Discussionsupporting
confidence: 70%
“…For some, the C-CELE reshaped their sociocultural context. This study's findings correlated with Baer, Smith, and Allen (2004), who revealed that experiential situations heighten emotional reaction and that emotional reaction toward content in association with experience generated profound levels of knowledge acquisition, which, according to the data from this study, had positive repercussions that transferred into awareness.…”
Section: Discussionsupporting
confidence: 70%
“…The Kentucky Inventory of Mindfulness Skills (KIMS) was used as manipulation check for the mindfulness intervention (Baer et al 2004). This instrument measures four mindfulness skills: observing, describing, acting with awareness, and accepting without judgment.…”
Section: Questionnairesmentioning
confidence: 99%
“…Current literature has highlighted the difficulty in defining the construct of mindfulness in self-report questionnaires (Baer, Smith, & Allen, 2004) and in selfreport assessment (Grossman, 2011). The understanding of a construct such as being in the moment or nonjudgmental awareness will differ from those with experience in mindfulness and those who are novices (Grossman, 2011).…”
Section: Discussionmentioning
confidence: 99%